STUDI TENTANG KEPUTUSAN NASABAH DALAM MENABUNG DI BANK SUMUT CABANG USU MEDAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Adli Nazrian; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2012)
The purpose of this study is to find out what are the driving factors of customers to deposit their money in Bank Sumut. The driving factors that analyzed in this research are availability of products, location, security,promotion, and the credibility of the bank. This research used primary data that collected through questionnaires distributed to 100 Bank Sumut customers. The research uses descriptive analysis and Analytical Hierarchy Process (AHP). The result of the research shows that the driving factors of customers to save in Bank Sumut ordinarily are availability of products, locations, security, credibility of the bank and promotion.